Dynamic Stretching does not Change the Stiffness of the Muscle-Tendon Unit - Mizuno, T.; Umemura, Y. (International Journal of Sports Medicine, 2016)
The purpose of this study was to identify changes in ankle range of motion and passive mechanical properties of the muscle-tendon unit after dynamic stretching. 12 healthy subjects participated in this study. Displacement of the muscle-tendon junction was measured using ultrasonography while the ankle was passively dorsiflexed at 1°/sec to its maximal dorsiflexion angle. Passive torque was also measured using an isokinetic dynamometer. Measurements were conducted pre-intervention, immediately after the intervention and 5, 10, 15 and 30 min post-intervention. The dynamic stretching consisted of four 30-s periods of ankle dorsiflexion and plantarflexion. Ankle range of motion was significantly increased immediately (from 18.3±1.8° to 21.4±1.7°) and 10 min (20.9±1.9°) after dynamic stretching, but this change disappeared within 15 min. However, stiffness of the muscle-tendon unit and displacement of the muscle-tendon junction at the submaximal dorsiflexion angle did not differ between the experimental conditions. These results demonstrate that dynamic stretching by contracting an antagonist muscle group increases ankle range of motion temporarily without changing the passive mechanical properties of the muscle-tendon unit. The increased range of motion of the ankle after dynamic stretching might be caused by enhanced stretch tolerance.
Keywords: passive mechanical properties; ultrasonography; passive torque; plantar flexors; stretch tolerance